Prognostic value of immune biomarkers in melanoma loco-regional metastases. - Emilia Hugdahl; Sura Aziz; Tor A Klingen; Lars A Akslen (PLoS ONE)
The prognosis for patients with melanoma loco-regional metastases is very heterogenous. Adjuvant PD-L1-inhibitors have improved clinical outcome for this patient group, but the prognostic impact of tumour PD-L1 expression and number of tumour infiltrating lymphocytes (TILs) is still largely unknown. Here, we investigated the impact on survival for CD3, CD8, FOXP3 and PD-L1 TIL counts and tumour PD-L1 expression in melanoma loco-regional metastases. In a patient series of loco-regional metastases from nodular melanomas (n = 78; n = 26 skin metastases, n = 52 lymph node metastases), expression of PD-L1 in tumour cells and the number of CD3, CD8, FOXP3 and PD-L1 positive TILs were determined by immunohistochemistry on tissue microarray (TMA) slides. Due to limited tumour tissue in the paraffin blocks, 67 of the 78 cases were included for tissue microarrays. Low FOXP3 TIL count and negative tumour PD-L1 expression (cut off 1%) were both significantly associated with reduced survival in lymph node metastases. Low FOXP3 TIL count was significantly associated with low CD8, CD3 and PD-L1 TIL counts. Negative tumour PD-L1 expression was significantly associated with low CD8 and PD-L1 TIL count, large lymph node metastasis tumour size and presence of necrosis in lymph node metastases. Our findings demonstrate for the first time the negative prognostic value of low FOXP3 TIL count and confirm a negative prognostic value of negative tumour PD-L1 expression in melanoma lymph node metastases.